'A mission he bore – to Duke William he came': Harold Godwineson's Commentum and his covert ambitions1. Issue 246 (27th June 2016) - van Kempen, Ad F. J.
Abstract: Harold Godwineson's journey to France, depicted on the Bayeux Tapestry, is nowadays mostly regarded as rather reckless attempt to free two hostages in Normandy. It is a curious incident, interrupting Harold's ascent to power in his homeland. William of Malmesbury's description of it as a fishing party has always been dismissed as a silly explanation. This article connects Malmesbury's phrase 'commentum' ('pretext') with other sources on the expedition. This comparison shows that Harold's boat trip and his intended diplomacy in France were not an interlude in his policy, but formed a continuation of his cautious, calculated manoeuvres towards possession of the English throne.